Responsibility of citizens in food safety social co-governance in the context of China - Wu, Linhai; Qin, Ke; Chen, Xiujuan (Frontiers in Public Health, 2022)
Objective This study aims to identify all actors that hold some responsibility for ensuring food safety based on the complete food supply chain in the context of China's current circumstances. Methods The study was conducted among citizens in Wuxi, Jiangsu, China. All citizens fully understood the purpose of the study and voluntarily agreed to participate. From December 10 to 14, 2020, a total of 398 valid samples were collected by the researchers using a structured questionnaire. Survey data were assessed using best–worst scaling and a mixed logit model from the perspective of citizen responsibility. Results In descending order, responsibility for ensuring food safety goes from food producers and traders (including producers, distributors, and retailers) to the government, social organizations, news media, and finally to citizens. Food producers and traders are the actors who should take the greatest responsibility, whereas citizens bear the least responsibility. Conclusion The responsibility of citizens in food safety co-governance should be recognized but it should not be arbitrarily extended.